دور أنظمة الرقابة الداخلية في الحد من مخاطر وسائل الدفع الإلكتروني في المصارف التجارية الليبية - أدهم عبدالولي حسين رحيل (Scientific Journal of University of Benghazi, 2020)
This study aims to identify the role of internal control systems in reducing the risks of electronic payment methods in Libyan commercial banks. For this purpose, a questionnaire was used to collect data from the study sample. The study used descriptive statistics methods by using iterations and percentages to describe the study sample. Also, it relied on inferred statistics by using a one-sample t-test. The finding showed that there is a role for internal control systems in reducing the risks of electronic payment methods in Libyan commercial banks. Consequently, several recommendations were recommended, and the most important of which is addressing the risks that were not taken into account in this study, to increase the knowledge about this topic.